Serum glutathione reductase level as a disease activity biomarker in systemic lupus erythematosus: a single-centre preliminary study - Yan Sun; Leixi Xue; Zhichun Liu; Mengxue Yan; Siping Li (Lupus Science and Medicine, 2025)
Objectives This study aimed to investigate serum glutathione reductase (GR) levels in patients with SLE and to assess its association with disease activity.Methods The retrospective study collected clinical data, including serum GR, complement (C) 3 and C4 levels, among patients with SLE. The SLE Disease Activity Index 2000 (SLEDAI 2000) and SLE Disease Activity Score (SLE-DAS) were calculated, and C3 and C4 were used as controls to assess the importance of serum GR levels in evaluating SLE disease activity.Results Serum GR levels were significantly higher in patients with SLE (n=142) than in healthy controls (n=100). Serum GR levels were positively correlated with SLEDAI 2000 (ρ=0.335) and SLE-DAS (ρ=0.454) values in patients with SLE. Further, C3 and C4 were negatively correlated with SLEDAI 2000 (ρ = −0.544 and −0.418) and with SLE-DAS (ρ = −0.290 and −0.242). Fisher’s Z test showed that GR was inferior to C3; however, similar to C4 in the correlation with SLEDAI 2000, whereas GR was comparable to C3 but superior to C4 in the correlation with SLE-DAS. The identification of moderate-to-severe disease activity based on SLEDAI 2000 of >6 revealed a receiver operating characteristic curve area under the curve (AUC) for GR of 0.700 (95% CI: 0.617 to 0.774), which was comparable to the AUC for C3 (0.784, 95% CI: 0.707 to 0.848) and C4 (0.697, 95% CI: 0.615 to 0.771); in determining moderate-to-severe disease activity as defined by SLE-DAS of >7.64, GR (0.767, 95% CI: 0.689 to 0.834) was equal to C3 (0.661, 95% CI: 0.576 to 0.738) but superior to C4 (0.617, 95% CI: 0.532 to 0.698).Conclusion Serum GR levels are positively correlated with SLE disease activity and exhibit clinical value in identifying moderate-to-severe disease activity in SLE.